(untitled) (Olhares, 2015)
The presence and importance of having the body and bodily (or physical) actions of the characters in the drama of Plínio Marcos. The analysis of the difference between body and flesh given by the French philosopher Michel Henri, through the scientific considerations of William James and John Dewey, American philosophers and psychologists. In addressing the aesthetics of the grotesque theater of Plínio Marcos, comes to an analysis of his theater that reconsiders its naturalistic aesthetics and allows other possibilities.